Nonlethal detection of Renibacterium salmoninarum in Greenback Cutthroat Trout Oncorhynchus clarkii stomias comparing mucus, blood, and ovarian fluid samples to kidney tissues - Firestone, Tawni B R (Journal of aquatic animal health, 2025)
© The Author(s) 2025. Published by Oxford University Press on behalf of American Fisheries Society.